2022
DOI: 10.3847/2041-8213/ac6beb
|View full text |Cite
|
Sign up to set email alerts
|

On the Energization of Pickup Ions Downstream of the Heliospheric Termination Shock by Comparing 0.52–55 keV Observed Energetic Neutral Atom Spectra to Ones Inferred from Proton Hybrid Simulations

Abstract: We present an unprecedented comparison of ∼0.52–55 keV energetic neutral atom (ENA) heliosheath measurements, remotely sensed by the Interstellar Boundary Explorer (IBEX) mission and the Ion and Neutral Camera (INCA) on the Cassini mission, with modeled ENAs inferred from interstellar pickup protons that have been accelerated at the termination shock, using hybrid simulations, to assess the pickup ion energetics within the heliosheath. This is the first study to use hybrid simulations that are able to accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 84 publications
1
31
0
Order By: Relevance
“…Giacalone & Decker (2010) show that such simulations produce a good agreement with the lower energy channels of Voyager 2 LECP measurements. Gkioulidou et al (2022) used an ENA model with a combination of different ion populations to reproduce the hybrid ion fluxes of Giacalone et al (2021) for the Voyager 2 direction. The ion distribution downstream of the termination shock was treated as two separate populations: transmitted PUIs with a kappa distribution and a combined reflected and accelerated PUI population with a kappa distribution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Giacalone & Decker (2010) show that such simulations produce a good agreement with the lower energy channels of Voyager 2 LECP measurements. Gkioulidou et al (2022) used an ENA model with a combination of different ion populations to reproduce the hybrid ion fluxes of Giacalone et al (2021) for the Voyager 2 direction. The ion distribution downstream of the termination shock was treated as two separate populations: transmitted PUIs with a kappa distribution and a combined reflected and accelerated PUI population with a kappa distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the modeled ENAs, for their best-fit model, differed from the observed ENAs of IBEX-Hi and INCA by an energy-dependent scaling factor. The discrepancy between modeled and observed ENA flux seen in other ENA models remained in the work of Gkioulidou et al (2022), despite improved modeling of the ion distribution downstream of the termination shock according to the hybrid model of Giacalone et al (2021). The authors concluded that some additional heating, or acceleration, of the PUI distribution in the heliosheath was necessary to replicate the data trend for all energies, especially at energies from 4 to 10 keV.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GDF, believed to primarily originate from the IHS, exhibits power lawlike spectra (Zirnstein et al 2021a). However, thus far, the total intensity of the observed GDF has proven challenging to recreate in models (Zirnstein et al 2017;Baliukin et al 2020;Fuselier et al 2021;Kornbleuth et al 2021;Gkioulidou et al 2022), suggesting the importance of turbulence at the HTS (Giacalone et al 2021;Zirnstein et al 2021b), an additional heating process in the IHS (Chalov et al 2003;Zirnstein et al 2018a), a separate ENA source from outside the heliopause (Izmodenov et al 2009;Opher et al 2013;Zirnstein et al 2014), or some combination of these. We address this issue by utilizing a dynamic model of PUI transport through the heliosphere to simulate the origin and evolution of IBEX ENA observations.…”
Section: Introductionmentioning
confidence: 99%